(untitled) (Cardiovascular Journal, 2019)
Background: Congenital heart diseases (CHD) are associated with an increased risk for the development of pulmonary vascular disease. Severe and irreversible pulmonary hypertension may then ensue and, eventually, leads to reversal of the shunt. Oral sildenafil is used for preoperative and postoperative treatment of pulmonary hypertension. Methods: A total of 30 patients, who underwent surgical closure of congenital anomaly i.e. ASD and VSD with High Pulmonary Pressure were included in the study. Patients were initially selected by echocardiogram showing pulmonary arterial systolic pressure (PASP) more than 40 mm of Hg. The Group A (sildenafil group) consisted of 15 patients and had received sildenafil during and after operation was given to these patients initially through nasogastric tube and later via the oral route 6 hourly for 44 hours. Results: Reduction in the PA pressure in sildenafil group was found statistically significant (p=.044). ICU stay and total hospital stay were shorter in the intervention group than the control but not statistically significant possibly due to smaller sample size. Conclusion: We conclude that oral sildenafil treatment is a safe, simple and effective alternate for persistent pulmonary hypertension early after congenital cardiac surgery. Cardiovasc. j. 2019; 12(1): 9-12